Skóra, która czuje - Momro, Jakub (Civitas. Studia z filozofii polityki, 2023)
The text is an attempt to approach the problem of desire from three sides: dialectical-political, psychoanalytic and deconstructive. In each of these paradigms of reflection, subjects become effective when they act within the framework of practical self-knowledge, which takes various forms: intentional alienation, elaboration of contradictions inherent in living environments, knowledge arising from the immanent unconscious and from the body exposed to touch.